2014
DOI: 10.11130/jei.2014.29.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Income Convergence and National Income Disparity : Europe, 1960~2012

Abstract: This study identifies income convergence in Europe over 1960 to 2012. The Great Recession since 2008 reversed the GDP per capita convergence in the EU-15, but the extransition countries have mostly continued to catch up. We found this by analysing the Sigma convergence of GDP per capita in the European Union. With a few pauses, there has been convergence in the European Union since 1960. Historically, convergence has been faster when aggregate GDP growth has been faster. On top of that, we link evolvement in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
(11 reference statements)
3
11
0
3
Order By: Relevance
“…6 Only in 1999 and 2009 did there appear to be a slight increase in the overall declining path. These results are consistent with the findings of Kaitila (2014). It can be concluded that the β-convergence rate found in the previous section did, in fact, lead to σ -convergence across the EU member states.…”
Section: Testing For σ -Convergencesupporting
confidence: 83%
“…6 Only in 1999 and 2009 did there appear to be a slight increase in the overall declining path. These results are consistent with the findings of Kaitila (2014). It can be concluded that the β-convergence rate found in the previous section did, in fact, lead to σ -convergence across the EU member states.…”
Section: Testing For σ -Convergencesupporting
confidence: 83%
“…In this work, on the basis of a panel of 33 countries covering the period from 1993 to 2012, a strong tendency for catching-up in the analysed group was confirmed. Additionally, many recent studies indicate a change in the convergence pace after the last crisis; see Kaitila (2014), Halmai and Vásáry (2012), Marelli and Signorelli (2015), Greta and Lewandowski (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sigma convergence can show convergence even if one country is for some reason left behind. The minimum value does not overlook this possibility (Kaitila 2013).…”
Section: Methodology and Datamentioning
confidence: 99%